1998
DOI: 10.1353/aad.2012.0098
|View full text |Cite
|
Sign up to set email alerts
|

The Deaf Mentor Experimental Project for Young Children Who Are Deaf and Their Families

Abstract: The Deaf Mentor Experimental Project investigated the efficacy of deaf mentor services to young deaf children and their families. These services focused on deaf adults (mentors), who made regular home visits to the children and their families; shared their language (American Sign Language), culture, and personal knowledge of deafness with the families; and served as role models for the children. The children also received regular home visits from a hearing parent adviser who helped the family promote the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Findings also suggest that communicative interactions are generally improved when a child has at least one parent who is also deaf or when parents have frequent contacts with deaf adults (Hintermair, 2000;Watkins, Pittman, & Walden, 1998). Hintermair found that parents who had frequent contact with deaf adults demonstrated increased interactional responsiveness to their child compared to parents who had no contact with deaf adults.…”
Section: Communicationmentioning
confidence: 90%
“…Findings also suggest that communicative interactions are generally improved when a child has at least one parent who is also deaf or when parents have frequent contacts with deaf adults (Hintermair, 2000;Watkins, Pittman, & Walden, 1998). Hintermair found that parents who had frequent contact with deaf adults demonstrated increased interactional responsiveness to their child compared to parents who had no contact with deaf adults.…”
Section: Communicationmentioning
confidence: 90%
“…An area that has been particularly deficient for families who choose ASL is access to an EI provider who is a fluent/native ASL signer*. 39,40 Families with children who are D/HH in the process of learning ASL require access to competent and fluent language models. In EI systems, competency and fluency are not ensured among EI providers.…”
Section: Share a Baseline Analysis Of Ehdimentioning
confidence: 99%
“…The known benefits of early sign language exposure do not have to be limited to a small percent of deaf children. Public health programs that incorporate deaf adult mentors can have positive outcomes for language and family well-being [36]. Further research on the role of having at least one deaf parent in a family and/or access to deaf adults would be useful for developing targeted strategies (such as a deaf mentor program) that holistically support hearing parents and family members in creating a healthy environment for the deaf child.…”
Section: Discussionmentioning
confidence: 99%